Delicious! [large type] : a novel - Reichl, Ruth (Thorndike Press, a part of Gale, Cengage Learning, 2014)
A New York Times Bestselling Author Billie Breslin traveled from her California home to take a job at Delicious, the most iconic food magazine in New York. When the publication is suddenly shut down, the staff, now Billie's extended family, must move on. But Billie is offered the job of staying behind in the deserted downtown mansion offices to uphold the "Delicious Guarantee." What she doesn't know is that this boring, lonely job will be the portal to a life-changing discovery.